Utilization of old meadow by reindeer in spring in northern Norway - Eilertsen, Svein M.; Schjelderup, Ivar; Mathiesen, Svein D. (Rangifer, 1999)
Utilization of abandoned coastal meadows in northern Norway by reindeer (Rangifer tarandus tarandus) were investigated for 25 days in spring 1996 (« = 12, 40-57 kg body mass (BM)) and 24 days in 1997 (» = 12, 39-61 kg BM). Grass production on grazed and ungrazed meadow was measured both years. Faecal dry matter (DM) production and ruminai in vitro DM digestibility (IVDMD) of selected plants were measured in the reindeer 15-22 days after the grazing experiment started each year. During the grazing period mean, standard deviation (s), temperature was 8.7, s = 2.8, °C in 1996 and 11.0, s = 3.0, °C in 1997, while temperature the first week was significantly higher in 1997 (P < 0.05). Mean herbage mass, on ungrazed meadow (control), after one week of plant growth in 1996 (408, J" = 166, kg DM ha"1) was significantly different (P < 0.05) from 1997 (576, s = 110, kg DM ha'). We believe the low temperature the first week in 1996 affected the plant production, and was the main reason for the significant (P < 0.05) difference in mean daily plant DM production on the grazed meadow between 1996 (57, s = 16, kg DM ha') and 1997 (81, s = 16, kg DM ha"1). Mean ruminai IVDMD of a mixture of meadow plants, differed (P<0.05) between 1996 (72.4, s = 1.0, %) and 1997 (83.9, s = 1.3, %), and mean daily food intake in 1996 (82, s = 13.5, g DM/kg0 75) was significantly lower than the intake in 1997 (131, s = 15.8, g DM/kg0 75). Daily digestible energy intake in reindeer was estimated to 0.96 Ml/kg07"5 X d 1 in 1996 and 1.85 Ml/kg""5 X d"1 in 1997, which was 1.3 and 2.5 times the resting metabolic rate in reindeer, respectively. We therefore assume the difference in food intake could be due to the initial difference in herbage mass.